2019
DOI: 10.1128/jb.00577-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Fifth Antibacterial Toxin Produced by a Single Bacteroides fragilis Strain

Abstract: Bacteroidales are the most abundant Gram-negative bacteria of the healthy human colonic microbiota, comprising nearly 50% of the colonic bacteria in many individuals. Numerous species and strains of gut Bacteroidales are present simultaneously at high concentrations in this ecosystem. Studies are revealing that gut Bacteroides has numerous antibacterial weapons to antagonize closely related members. In this study, we identify a new diffusible antibacterial toxin produced by Bacteroides fragilis 638R, designate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…41 Bfr strains either possess the bsap-1 gene encoding the toxin, or they lack the gene and are sensitive to it. 42 Producers of BSAP-1 have a gene adjacent to the bsap-1 gene that encodes an orthologue of the target outer membrane protein that serves as the receptor for BSAP-1 in the target bacterium. 43 This orthologue is structurally similar to the target receptor but is sufficiently different, so as not to be targeted by the toxin, but to protect the producer from it.…”
Section: Antimicrobial Toxins Are Used In Bacterial Competitionmentioning
confidence: 99%
“…41 Bfr strains either possess the bsap-1 gene encoding the toxin, or they lack the gene and are sensitive to it. 42 Producers of BSAP-1 have a gene adjacent to the bsap-1 gene that encodes an orthologue of the target outer membrane protein that serves as the receptor for BSAP-1 in the target bacterium. 43 This orthologue is structurally similar to the target receptor but is sufficiently different, so as not to be targeted by the toxin, but to protect the producer from it.…”
Section: Antimicrobial Toxins Are Used In Bacterial Competitionmentioning
confidence: 99%
“…A small inhibition zone was observed, corresponding to the size of the original bacterial spot, demonstrating that Bf 9343 produces an additional antimicrobial toxin, as is typical of B. fragilis strains (59, 60). These analyses show that pLGB30 allows for easy creation of double-crossover mutants in erythromycin-resistant strains where tetracycline selection of cointegrates is necessary.…”
Section: Resultsmentioning
confidence: 95%
“…Analyses of recent human fecal isolates of Bacteroidales with interesting phenotypes revealed that many are resistant to both tetracycline and erythromycin (60, 65) and therefore are not amenable to genetic manipulation using available genetic tools for these bacteria. We evaluated tetracycline and erythromycin resistance among 120 Bacteroides strains from our collection isolated between 2009 and 2011 from the stool of 15 healthy U.S.-resident adults with no history of gastrointestinal diseases (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cholesterol-dependent cytolysin (CDCs) are a family of β-barrel pore-forming toxins expressed by many Gram-positive pathogens, but only identified in a few Gram-negative terrestrial bacteria to date ( 1 ). The CDCs share a domain 3 (D3) protein fold with many evolutionarily distant proteins, including members of the mammalian membrane attack complex/perforin family (MACPF) ( 2 7 ). This structural domain is characterized by a core β-sheet flanked by two contiguous α-helical bundles (αHBs) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…fold with many evolutionarily distant proteins, including members of the mammalian membrane attack complex/perforin family (MACPF) (2)(3)(4)(5)(6)(7). This structural domain is characterized by a core ␤-sheet flanked by two contiguous ␣-helical bundles (␣HBs) (Fig.…”
mentioning
confidence: 99%